From the system of National Accounts (SNA) to a Social Accounting Matrix (SAM) - based model : an application to Portugal - Santos, Susana (2017)
A Social Accounting Matrix (SAM), in both its numerical and algebraic versions, will be proposed as a working instrument for studying the (macro-)impacts of government policies on the distribution of income, paying close attention to the corresponding response of the different macroeconomic aggregates, balances and indicators. For the geographical limits of Portugal and a time limit of one year (1 January to 31 December), a SAM is constructed from the SNA 93 (1993 version of the United Nations System of National Accounts) within an ESA 95 (European System of National and Regional Accounts in the European Community of 1995) framework. It will be shown that underlying the SAM are interrelated subsystems that, in its numerical version, provide an analytical picture of the circular flow or the general equilibrium interactions of a market economy (Portugal, in this case) when studied in a particular accounting period, while, in its algebraic version, these same subsystems make it possible to measure and quantify the economy-wide effects of changes in the particular nominal flows represented by the numerical version (injections into and leakages from the system), which might be the result of policy measures.